2007
DOI: 10.1038/sj.bjc.6604062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 18F-2-deoxy-2-fluoro-glucose positron emission tomography for gastric cancer screening in asymptomatic individuals undergoing endoscopy

Abstract: 18 F-2-deoxy-2-fluoro-glucose Positron Emission Tomography (FDG-PET) has been recently proposed as a promising cancerscreening test. However, the validity of FDG-PET in cancer screening has not been evaluated. We investigated the sensitivity of FDG-PET compared with upper gastric endoscopy in gastric cancer screening for asymptomatic individuals. A total of 2861 consecutive subjects (1600 men and 1261 women) who were asymptomatic and who underwent both FDG-PET and upper gastrointestinal endoscopy between 1 Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…Notably, in our study, 29 gastric cancers that were not detected on PET/CT imaging were all MSS gastric cancers. Although there are several studies that have shown different degrees of FDG uptake in primary gastric cancer on PET imaging [3,[11][12][13], this is the first study that shows the significance of MSI in detecting gastric cancers using PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in our study, 29 gastric cancers that were not detected on PET/CT imaging were all MSS gastric cancers. Although there are several studies that have shown different degrees of FDG uptake in primary gastric cancer on PET imaging [3,[11][12][13], this is the first study that shows the significance of MSI in detecting gastric cancers using PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…For gastric cancers, FDG-PET imaging provides important additional information concerning the prognosis of recurrent cancer, including lymph node metastases, peritoneal carcinomatosis, distant metastasis, tumor response to treatment, and overall survival [3][4][5][6][7][8][9][10]. However, some subtypes of gastric cancer exhibit reduced FDG uptake [3,[11][12][13][14], which significantly limits the use of PET in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity for LNs is improved when uptake of FDG is high by the primary tumor [14,15]. Specificity for both the primary tumor and metastatic LNs is consistently very high (90-100%) [15,20,23], which is better than the specificity of CT [14]. Staging accuracy, and hence decision-making, is improved when PET and CT are both utilized rather than either alone [14].…”
mentioning
confidence: 89%
“…FDG PET sensitivity for gastric tumors is typically reported to be the same or poorer than CT (45-95% for PET), but depends greatly on the tumor stage (T1 poorer than T2-T4) [14,20], histological type (mucinous worse than non-mucinous) [14,15,21,22], and appears to be directly related to the expression of the glucose transporter-1 (GLUT-1) [22]. Hence, PET is not an appropriate screening tool [20]. Sensitivity for metastatic LNs in the context of gastric cancer is approximately 30-60%, and ranges from 8 to 88% when separated into locoregional and distant nodes.…”
mentioning
confidence: 99%
“…Of these, 11 were malignant tumors, including 3 gastric cancers, 2 small bowel cancers, and 6 colon cancers. Shoda et al [50] compared the sensitivity of PET with that of upper gastric endoscopy in gastric cancer screening for 2861 asymptomatic subjects. Positive PET results were obtained in only 2 of 20 (10%) patients with gastric cancer, including 18 T1 tumors.…”
Section: Efficacy Of Pet For the Screening Of Gastric Cancermentioning
confidence: 99%